A Floristic Account of Ludhiana District (Punjab) - Sharma, M.; Sharma, O. P. (Indian Forester, 1974)
The present paper, besides giving a brief description of topography, soils, climate, biotic factors and method of exploration; gives a detailed account of the vegetation of botanically unexplored Ludbiana District of Punjab.